Nurses experience of caring for patients with COVID-19: A phenomenological study - Al-amer, Rasmieh; Darwish, Maram; Malak, Malakeh; Ali, Amira Mohammed; Al weldat, Kadejeh; Alkhamees, Abdulmajeed; Alshammari, Khaled S.; Abuzied, Yacoub; Randall, Sue (Frontiers in Psychiatry, 2022)
Introduction: COVID-19 has impacted all dimensions of life and imposed serious threat on humankind. Background: In Jordan, understanding how nurses experienced providing care for patients with COVID-19 offers a framework of knowledge about similar situations within the context of Arabic culture. Aim: To explore nurses’ experience with providing hands-on care to patients with active COVID-19 infection in a collectivist society. Methods: A descriptive phenomenological study interviewed ten nurses through a purposive sampling approach. Findings: Three themes were generated from the data: the impact of the COVID-19 outbreak on nurses’ health; unfamiliar work and social environments; and conforming to professional standards. Discussion: There are specific risks to the physical and mental wellbeing of nurses who provide hands-on care to patients with COVID-19 in a collectivist society. Implication for Nursing and Health Policy: Health care institutions should consider establishing programs that promote nurses’ well-being and support their productivity in a crisis. A danger pay allowance should be considered for nurses during extraordinary circumstances, such as pandemics.